ANTIDIABETIC ACTIVITY FROM TABLETS EFFERVESCENT EXTRACT OF MIMOSA PUDICA LINN LEAVES - Na'ilatul Azizah; Ika Buana Januarti; Annisa Masithoh; Anna Khoirun Nisa (Jurnal Farmasi Sains dan Praktis, 2020)
The community has trusted mimosa pudica linn as an alternative antidiabetic treatment. Compounds that have antidiabetic activity in Mimosa pudica linn are flavonoids, alkaloids, and tannins. The selection of effervescent tablet dosage formulations is practical for diabetics with the addition of stevia leaf sweeteners. This study aimed to determine the antidiabetic activity of effervescent tablets of Mimosa pudica linn leaves extract as a natural antidiabetic. The research method begins with the extraction of plants using the maceration method of 70% ethanol; the tablet formulation uses dry granulation. Antidiabetic activity test using 28 male mice (Mus musculus) Swiss strain divided into four groups, namely group I (negative control): Na-CMC 0.5%, group II: effervescent tablets of Mimosa pudica Linn leaves Extract dose 600 mg/kgBB, group III (positive control): metformin 65 mg/kgBB, group IV (normal control): feed and drink. Each group, except normal controls, was induced by DM using alloxan 150 mg/kg body weight. Data on decreased blood glucose levels were analyzed using the Kruskal-Wallis statistical test the study results show that effervescent tablets meet the parameters of disperse time test, pH test, size uniformity test, weight uniformity test, hardness test, moisture test, and friability test. This study concludes is that there is a significant difference between the negative, positive, normal, and treatment control groups, which means that the administration of effervescent tablets of 70% ethanol extract of Mimosa pudica Linn leaves at a dose of 600 mg/kgBB can reduce blood sugar levels in mice (Mus musculus).